Construction of an instrument for evaluating the teaching process in higher education: Content and construct validity - Risky Setiawan; Wagiran Wagiran; Yasir Alsamiri (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2024)
This study aims to reveal the content validity, construct validity, and reliability of the instrument for evaluating the teaching process in higher education. This research is development research applying the ADDIE model from Molenda. The indicators evaluated consist of context, inputs, processes, and products. The sample consisted of 1200 students from eight faculties, each represented by three study programs. Data analysis uses three stages: content validity test analysis using the V -Aiken method involving six panellists or experts; construct validity test using Confirmatory Factor Analysis (CFA). Quantitative descriptive analysis and interpretive qualitative analysis used the Miles and Huberman method. The results showed that the developed evaluation instrument had good proof of the validity of the content, with an average V-Aiken score of 0.752, which was in the high category. Universitas Negeri Yogyakarta's evaluation instrument, which was developed through the instrument, already meets the validity of an exemplary construct of a good loading factor value (> 0.3). It has a composite reliability score above 0.7 and Cronbach's alpha above 0.6. The analysis results show that all empirical test criteria indicate the data is fit against the developed model.